SMART INVESTMENT EDUCATION FOR MEMBERS OF THE DIAN HUSADA CONSUMER COOPERATIVE IN DEMAK REGENCY - Adhi, Daniel Kartika; Wahyuningsih, Panca; Tasriastuti, Nurrohmi Ambar (STIE Pelita Nusantara, 2025)
This community service program aims to improve the financial literacy and investment skills of members of the Dian Husada Consumer Cooperative, Demak Regency, through the “Smart Investment Education” initiative. The program was motivated by the low understanding among members of legal investment instruments and the lack of long-term financial planning. The methods applied include participatory training, risk profile simulations, and assistance in preparing personal investment plans. The activity resulted in a 72% improvement in members’ understanding of investment concepts, behavioral changes reflected in increased member savings, and greater awareness of the importance of investment products supervised by the Financial Services Authority (OJK). This article emphasizes that cooperatives can play a strategic role as financial education centers for their members and as partners to regulators in building financially literate communities.Keywords: financial literacy, investment, cooperative, economic empowerment, OJK